Dexamethasone mediates pancreatic cancer progression by glucocorticoid receptor, TGF β and JNK/AP-1 - Liu, Li; Aleksandrowicz, Ewa; Schönsiegel, Frank; Gröner, Daniel; Bauer, Nathalie; Nwaeburu, Clifford C.; Zhao, Zhefu; Gladkich, Jury; Hoppe-Tichy, Torsten; Hackert, Thilo; Strobel, Oliver; Herr, Ingrid (Cell death & disease, 2017)
Glucocorticoids such as dexamethasone are widely co-prescribed with cytotoxic therapy because of their proapoptotic effects in lymphoid cancer, reduction of inflammation and edema and additional benefits. Concerns about glucocorticoid-induced therapy resistance, enhanced metastasis and reduced survival of patients are largely not considered. We analyzed dexamethasone-induced tumor progression in three established and one primary human pancreatic ductal adenocarcinoma (PDA) cell lines and in PDA tissue from patients and xenografts by FACS and western blot analysis, immunohistochemistry, MTT and wound assay, colony and spheroid formation, EMSA and in vivo tumor growth and metastasis of tumor xenografts on chicken eggs and mice. Dexamethasone in concentrations observed in plasma of patients favored epithelial–mesenchymal transition, self-renewal potential and cancer progression. Ras/JNK signaling, enhanced expression of TGFβ, vimentin, Notch-1 and SOX-2 and the inhibition of E-cadherin occurred. This was confirmed in patient and xenograft tissue, where dexamethasone induced tumor proliferation, gemcitabine resistance and metastasis. Inhibition of each TGFβ receptor-I, glucocorticoid receptor or JNK signaling partially reversed the dexamethasone-mediated effects, suggesting a complex signaling network. These data reveal that dexamethasone mediates progression by membrane effects and binding to glucocorticoid receptor.